PERCEPTION OF DIRECT AND INDIRECT COMPENSATIONS FULFILLMENT ON HAZARDOUS WORK ENVIRONMENT: THE RELATIONSHIP WITH AGE, TENURE, EMPLOYEE’S RANK AND WORK STATUS - Setyabudi Indartono; Chun-Hsi Vivian Chen (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2008)
This paper investigates how ages, tenure, employee’s rank and work status related to perception of direct and indirect compensations fulfillment in a hazardous work environment. This study found that age, tenure, employee’s rank and work status are positively related to perception of direct and indirect compensations fulfillment. Implication for research and practice are discussed.Keywords: Demographic characteristics, direct and indirect compensations, Hazardous work environment